Evaluation of Technical and Anthropometric Factors in Postures and Muscle Activation of Heavy-Truck Vehicle Drivers: Implications for the Design of Ergonomic Cabins - Esteban Ortiz; Daysi Baño-Morales; William Venegas; Álvaro Page; Skarlet Guerra; Mateo Narváez; Iván Zambrano (Applied Sciences, 2025)
This study investigates how three technical factors—steering wheel tilt, torque, and cabin vibration frequency—affect driver posture. Heavy-truck drivers often suffer from musculoskeletal disorders (MSDs), mainly due to poor cabin ergonomics and prolonged postures during work. In countries like Ecuador, making major structural changes to cabin design is not feasible. These factors were identified through video analysis and surveys from drivers at two Ecuadorian trucking companies. An experimental system was developed using a simplified cabin to control these variables, while posture and muscle activity were recorded in 16 participants using motion capture, inertial sensors, and electromyography (EMG) on the upper trapezius, middle trapezius, triceps brachii, quadriceps muscle, and gastrocnemius muscle. The test protocol simulated key truck-driving tasks. Data were analyzed using ANOVA (<semantics><mstyle scriptlevel="0" displaystyle="true">p<0.05</mstyle></semantics>), with technical factors and mass index as independent variables, and posture metrics as dependent variables. Results showed that head mass index significantly affected head abduction–adduction (<semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>8.12 to <semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>2.18°), and spine mass index influenced spine flexion–extension (<semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>0.38 to 6.99°). Among technical factors, steering wheel tilt impacted trunk flexion–extension (<semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>13.56 to 16.99°) and arm rotation (<semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>31.1 to 19.7°). Steering wheel torque affected arm rotation (<semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>30.49 to <semantics><mstyle scriptlevel="0" displaystyle="true">−</mstyle></semantics>6.77°), while vibration frequency influenced forearm flexion–extension (3.76 to 16.51°). EMG signals showed little variation between muscles, likely due to the protocol’s short duration. These findings offer quantitative support for improving cabin ergonomics in low-resource settings through targeted, cost-effective design changes.